Volvopluteus canalipes comb. nov. (Pluteaceae) from the Sonoran Desert of Mexico - Montoya, Leticia; Bandala, Victor M.; Esqueda, Martin (Phytotaxa, 2021)
A collection of a volvarioid species with whitish, medium-sized basidiomes and distinctive grooved stipe was found in sandy soil in the Sonoran Desert, northwest of Mexico. After a morphological comparison with the type specimen of Volvariopsis canalipes from Florida, USA, we found that both materials share a similar set of taxonomic characters that supports considering them to be conspecific. Some species formerly placed in Volvariella but characterized by a gelatinous pileipellis and large basidiospores (such as V. canalipes) are currently recognized in Volvopluteus. A phylogenetic analysis based on ITS and LSU sequences obtained from the Sonoran material, inferred its position in Volvopluteus and sister to Vp. gloiocephallus. Based on morphological and molecular information, the new combination Volvopluteus canalipes is proposed. This corresponds to the second record of this species after its original publication. A description of the Mexican collection accompanied with photographs and line drawings is included and complemented with a taxonomic discussion.